2021
DOI: 10.1016/j.hlc.2021.05.108
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, Hypertension and Aortic Valve Stenosis: A Conscious Uncoupling

Abstract: Aortic valve stenosis (AS) is no longer considered to be a disease of fixed left ventricular (LV) afterload (due to an obstructive valve), but rather, functions as a series circuit with important contributions from both the valve and ageing vasculature. Patients with AS are frequently elderly, with hypertension and a markedly remodelled aorta. The arterial component is sizable, and yet, the contribution of ventricular afterload has been difficult to determine. Arterial stiffening increases the speed of propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Despite the accessibility of Z VA and its widespread use, the technique has limitations including: (i) the potential for underestimation of flow velocity due to misalignment of the Doppler signal with flow direction; (ii) the risk of underestimation of LV outflow tract diameter due to inadequate quality and/or positioning of the imaging plane; (iii) measurement variability related to manual tracing of flow velocity contours, and; (iv) the calculation of mean pressure from brachial cuff pressure rather than direct measurement of central aortic pressure [12]. Furthermore, Z VA is measured as the ratio of pressure to indexed volume (rather than pressure to flow) and may therefore be more accurately described as a resistance index rather than a true measure of vascular impedance (Figure 2).…”
Section: Echocardiographic Methods To Determine Vascular Impedancementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the accessibility of Z VA and its widespread use, the technique has limitations including: (i) the potential for underestimation of flow velocity due to misalignment of the Doppler signal with flow direction; (ii) the risk of underestimation of LV outflow tract diameter due to inadequate quality and/or positioning of the imaging plane; (iii) measurement variability related to manual tracing of flow velocity contours, and; (iv) the calculation of mean pressure from brachial cuff pressure rather than direct measurement of central aortic pressure [12]. Furthermore, Z VA is measured as the ratio of pressure to indexed volume (rather than pressure to flow) and may therefore be more accurately described as a resistance index rather than a true measure of vascular impedance (Figure 2).…”
Section: Echocardiographic Methods To Determine Vascular Impedancementioning
confidence: 99%
“…where |Z in | = |P|÷|Q| is the modulus and θ = (βϕ) is the phase of the impedance [10,11]. Both the steady-state and pulsatile load contribute to the total hydraulic load of the systemic circulation [12].…”
Section: Defining Hydraulic Load Of the Human Circulationmentioning
confidence: 99%
“…Thus, AS is a clinical marker of NO resistance and of coronary risk. This is not particularly surprising given that NO also functions to retard the development of aortic valve calcification [68][69][70][71].…”
Section: Aortic Valve Stenosismentioning
confidence: 98%
“…A number of recent studies have demonstrated that the aging process is closely associated with extensive inflammatory activation and this inflammation, in turn, contributes to age-related increases in incidence of many forms of cardiovascular and cerebrovascular disease [69,79].…”
Section: Agingmentioning
confidence: 99%
“…The traditional view that AS is a fixed, valvular LV outflow obstruction has recently been challenged by the concept that LV afterload is a series circuit involving both the valve and the vasculature [ 5 ], with an emphasis on ventriculo-valvulo-arterial coupling. Quantification of the vascular load in AS is nebulous, as current methods of afterload assessment typically focus on the LV or the valve itself in isolation, and often underestimate the effect of the vascular load [ 6 ]. Separation of pulsatile and steady state arterial load is rarely performed in the assessment of vascular load, especially in the context of AS.…”
Section: Introductionmentioning
confidence: 99%